Digital Transformation in Educational Management for School Quality in the Digital Era - Ilyas, Ilyas; Wahab, Wahab; Imran, Imran; Mahluddin, Mahluddin; Asmawati, Asmawati (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study explores the phenomenon of digital transformation in educational management by examining its opportunities, challenges, and implications for school quality. The purpose of this study is to provide a comprehensive analysis of how digital tools and platforms are reshaping school governance, pedagogy, and policy. Using a qualitative literature review method, data were collected from national and international scholarly articles, policy documents, and academic reports published between 2019 and 2025. A total of ten carefully selected articles were analyzed using content analysis to identify thematic patterns related to digital transformation in schools. The findings reveal that digital technologies such as Learning Management Systems (LMS), AI-powered tools, and data-driven dashboards improve school efficiency, stakeholder engagement, and personalized learning. However, the study also uncovers significant challenges, including unequal access to digital infrastructure, limited digital literacy among educators, institutional resistance to change, and cybersecurity risks. The results underscore that the success of digital transformation depends not only on technological readiness but also on leadership vision, inclusive strategies, and sustained digital policy planning. This study contributes theoretically to the discourse on digital educational leadership and practically to school-based digital transformation strategies in the digital era.